TEXTUAL-SKRIPTUAL GROUP PARADIGM AGAINST THE CONCEPT OF ISLAMIC WASATIYAH: A CASE STUDY OF THE ISLAM DEFENDER FRONT (FPI) IN INDONESIA - Jamarudin, Ade; Pudin, Ofa Ch; Dewi L, Ella; Syehabudin, Abud; Tentri, Tentri (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2022)
Wasathiyah Islam can be called moderate Islam. The meaning of Wasathiyah itself is an attitude that requires a person to do two things, namely knowledge and holding back emotions. Islam Wasathiyah is a model of expression and understanding that is relevant in the framework of statehood in Indonesia. Indonesia is a Muslim majority religion in which there are several Islamic organizations and have different opinions in understanding modern Islam, but the understanding can be different. Islamic organizations have contributed to understanding Islam as rahmatanlilalamin. Indonesian Muslim communities present offer the concept of Islam Wasatiyah in building Islamic civilization as an effort to build peace and implement the values of Unity in Diversity. The Islamic world is confronted with groups that hold fast to the text and ignore the socio-historical aspects in carrying out religious teachings which then declare themselves to be holders of religious authority. This article will reveal and analyze the paradigm of textual-scriptual groups towards the values contained in the Wasatiah Islamic concept. Religious experience in Indonesia that adopts the values of Pancasila by promoting cultural-philosophical aspects is often considered to be far from the purity of Islam. Descriptive analysis method is used to describe and analyze the paradigms of groups that tend to understand the written source as it is by ignoring the circumstances and the conditions underlying it. The results of this study are (1) Islam Wasatiyah is a religious experience in Indonesia that internalizes local wisdom into Islamic teachings (2) The monopoly of truth and the rationalization of the term were never done by the Prophet without regard to the context of being a challenge in the implementation of Wasatiyah Islam (3) Textual Group- Scriptures tend to distort the understanding of the Qur'an and Hadith so that they ignore themes related to peace and tolerance.